Resilient and Sustainable Farming Systems in Europe 2022
DOI: 10.1017/9781009093569.018
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Assessment of the Sustainability and Resilience of Farming Systems

Abstract: Lessons from the Past and Ways Forward for the Future f r a n c e s c o a c c a t i n o , w i m p a a s , h u g o h e r r e r a , c o r e n t i n p i n s a r d , s i m o n e s e v e r i n i , f r a n z i s k a a p p e l , b i r g i t k o p a i n s k y , k a t a r z y n a b a n ´kowska, jo bijttebier, camelia gavrilescu, amr khafagy, vitaliy krupin, gordana manevskatasevska, franziska ollendorf, mariya peneva, carolina san martı ´n, cinzia zinnanti and pytrik reidsma 282Accatino,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Building resilient agricultural systems relies on innovation, networks, and collaboration [27]. Innovation can be defined and measured narrowly in terms of research and development or technological improvements linked to the development of new products and processes [28].…”
Section: The Role Of Innovation and Knowledge Transfer In Building Re...mentioning
confidence: 99%
“…Building resilient agricultural systems relies on innovation, networks, and collaboration [27]. Innovation can be defined and measured narrowly in terms of research and development or technological improvements linked to the development of new products and processes [28].…”
Section: The Role Of Innovation and Knowledge Transfer In Building Re...mentioning
confidence: 99%
“…We organized a participatory workshop for stakeholders in the Bourbonnais farming system in February 2019, called FoPIA-SURE-Farm 1 (see Accatino and Neumeister, 2019). The stakeholders assessed the importance and performance of the functions provided by the farming system.…”
Section: Beef Production In a Beautiful Landscape: Where Is The Trade...mentioning
confidence: 99%
“…The first Label Rouge farm in the Bourbonnais was certified in 1974, and since then many more have subscribed. Production under label follows specific Source: Data from Accatino and Neumeister (2019) rules, such as type of feed, grazing period, and minimum slaughter age.…”
Section: Quality Of Beef: a Long Tradition In The Bourbonnais Areamentioning
confidence: 99%
“…Among these, sustainability-related activities are an important element embedded in the resilience cycle (Darnhofer et al, 2010). In particular, stakeholders within the agricultural system show a strong interest in this combination of sustainability and resilience (Accatino et al, 2022). For example, empirical evidence has confirmed that the resilience of organic agriculture exceeds that of conventional agricultural practices (Herman et al, 2018;Grigorescu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Sustainability practices shape the fundamental attributes of farm resilience, including stakeholder management, innovation, human resource development, and diversification into various businesses (Meuwissen et al, 2018). In addition, case studies show that sustainability practices and resilience in a farm system are mutually reinforcing (Accatino et al, 2022). However, there is a lack of research quantifying the relationship between sustainability practices and farm resilience.…”
Section: Introductionmentioning
confidence: 99%